Impedance analysis of film-forming amines for the corrosion protection of a carbon steel. (1st September 2018) - Baux, Jordan; Caussé, Nicolas; Esvan, Jérôme; Delaunay, Sophie; Tireau, Jonathan; Roy, Marion; You, Dominique; Pébère, Nadine
Abstract: Octadecylamine (ODA) is a well-known organic inhibitor for the corrosion protection of carbon steels. In the present study, electrochemical impedance data analysis was performed to extract physical parameters of the ODA thin film that formed on a P275 carbon steel surface. First, surface observations and contact angle measurements showed the steel surface modification after the ODA treatment linked to the adsorption of an organic hydrophobic thin film. X-ray photoelectron spectroscopy confirmed the presence of a very thin organic layer and revealed the presence of iron oxide/hydroxide underlying the ODA film. The impedance data analysis with a power-law distribution of resistivity in the organic film allowed the permittivity and thickness to be extracted. Finally, from the impedance results with and without ODA, the instantaneous corrosion inhibition efficiency was determined.